How do microRNAs regulate gene expression?. (19th November 2008) - Cannell, Ian G.; Kong, Yi Wen; Bushell, Martin
Abstract : miRNAs (microRNAs) are short non-coding RNAs that regulate gene expression post-transcriptionally. They generally bind to the 3′-UTR (untranslated region) of their target mRNAs and repress protein production by destabilizing the mRNA and translational silencing. The exact mechanism of miRNA-mediated translational repression is yet to be fully determined, but recent data from our laboratory have shown that the stage of translation which is inhibited by miRNAs is dependent upon the promoter used for transcribing the target mRNA. This review focuses on understanding how miRNA repression is operating in light of these findings and the questions that still remain.